Hamstring injury prevention: A role for genetic information?. (October 2018) - Pickering, Craig; Kiely, John
Abstract: Hamstring Strain Injuries (HSI) are common within many sports, imposing a significant burden in terms of both financial cost, recovery time, and loss of performance. Recently, research has focused on better understanding the factors that increase an individual's risk of suffering a HSI, with both lower strength (particularly eccentric strength) and shorter hamstring muscle fascicles found to play a significant role. Such findings have led to an increased popularization of eccentric hamstring exercises, such as the Nordic Hamstring Exercise, the correct utilization of which has been shown to reduce HSI rates. However, despite the robust evidence of their efficacy, adherence to eccentric loading exercises is often poor, with concerns about soreness often cited. Here, we advance the hypothesis that the utilization of genetic information will, in the future, allow for the optimization of HSI prevention programmes, both in terms of training adaptations, and both muscle damage and soreness in the acute phase of post-training recovery. We also discuss whether this information could be utilised in sport in order to predict HSI injury. Such an hypothesis, if correct, could have important implications for the implementation of injury prevention programmes, particularly with regards to adherence, which evidence suggests is currently a major barrier to the utilization of eccentric hamstring exercises.